Technology and Sustainable Development: The Promise and Pitfalls of Techno-Solutionism - Henrik Skaug Sætra (CRC Press, 2023)
governance;politics;Sustainable development goals;sustainability;technological change
Keywords: 320; governance; politics; Sustainable development goals; sustainability; technological change